x+70=60

Simple and best practice solution for x+70=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+70=60 equation:


Simplifying
x + 70 = 60

Reorder the terms:
70 + x = 60

Solving
70 + x = 60

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-70' to each side of the equation.
70 + -70 + x = 60 + -70

Combine like terms: 70 + -70 = 0
0 + x = 60 + -70
x = 60 + -70

Combine like terms: 60 + -70 = -10
x = -10

Simplifying
x = -10

See similar equations:

| 50000=((x*1.3)+x) | | 8-5x-x=4+x-x | | -124+25x=151 | | x+60=54 | | 10/9x9/16 | | ((4^3)^2)/16 | | 3x-16=7x+9 | | f(x)=x^5+25x^4-37x^3-200x^2+48x+10 | | -3y+7z=-5 | | (4^3)^2/16 | | 3(2x-4)=2(3x-1) | | 9y^2-4y=10 | | f(8)=x^2-x+3 | | 2sinx-2^1/2=0 | | -19(g-996)=475 | | y=4d+6 | | 2sinx-2^1/2 | | (5u+2)(9-u)=0 | | 214=34+15r | | Y=-.03x-1.8x+45 | | 17+27m=638 | | -2(y+6)=5 | | Patrick= | | 65-27y=902 | | 2a+3=3 | | 3x(2x-3)(3x-4)=0 | | 8(q-852)=600 | | 1/2*2x-10=22 | | 6x-3+8x=-11 | | 2x+100=x+52 | | 0.3x-9=(0.6x+4) | | 961=15y-91 |

Equations solver categories